Policy Hotspots for Islamic Green Finance: Navigating the Global Path to Economic Sustainability - Lia Kian; Sofyan Abas; Rafiqah; Arphandee Hasan (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2026)
This study examines the implementation of Islamic green finance through a policy hotspot framework that emphasizes synergy among regulators, Islamic financial institutions, and business actors within the green financing ecosystem. Using a qualitative library-based method with normative, conceptual, and content analysis approaches, this research analyzed secondary data from reports and studies published by the United Nations Environment Programme (UNEP), IMF, World Bank, ICMA, UNDP, IPCC, EIU, and relevant prior studies from 2018 to 2025. The data focused on the development of green finance and Islamic green finance in Europe, Asia, and selected Islamic countries, including Saudi Arabia, the United Arab Emirates, Indonesia, and Malaysia. Based on post-Paris Agreement developments (2018–2022), this study proposed an Islamic green finance model for house building as a policy hotspot to navigate the global path toward sustainable development with social, economic, and environmental impacts. The proposed model consists of four key pillars: (1) Islamic values and principles, including maqāṣid al-sharīʿah, justice (adl), and balance (mizan); (2) Islamic financial instruments such as green sukuk, productive zakat, cash waqf, murabahah, and green ijarah; (3) regulatory and policy support involving green taxonomy, central banks, financial authorities, and ulema councils; and (4) integrated policy implementation grounded in sharia principles. This model is expected to serve as a reference for Indonesia and other countries in developing inclusive and sustainable Islamic green finance.